Fortifying Biosafety in Nigeria: Insights and Transformative Practices from the SNL-NIBSA Bio-risk Management Course - Ishaku Leo Elisha; Ahmed Waleed Joyan (Babcock University Medical Journal)
This study highlights the critical role of biosafety and biosecurity in scientific advancement and public health protection. It stresses responsible research conduct and risk mitigation. Biorisk management systematically identifies, assesses, and mitigates biohazard risks, ensuring safety for personnel and the environment. Collaboration between Sandia National Laboratories (SNL) and the Nigerian Biological Safety Association (NiBSA) boosts international cooperation and biosafety standards. The SNL-NiBSA Biorisk Management Course in Lagos addresses Nigerian challenges with practical solutions. Key learnings emphasize risk assessment, lab practices, protective gear use, and waste management. Identified challenges prompt education enhancement, resource optimization, and international collaboration. Potential outcomes include replicated training programs, local guidance documents, policy advocacy, and regional cooperation. Overall, SNL-NiBSA collaboration elevates biosafety, promotes responsible research, and enhances global health security.